The Effects of Public - Private Partnership Act on the Slovenian Public Utilities Providers - Veronika Petkovšek; Primož Pevcin (Central European Public Administration Review)
The paper presents the legal status of existing public enterprises in Slovenia before and after the adoption of Public-Private Partnership Act, that demanded the reorganization of existing public enterprises in the period 2007-2009. The paper also presents the analysis of local public utilities delivery mechanisms in Slovenia, focusing on the local public utilities providers in the field of water and waste management. The aim of the paper is to introduce the changes in the legal status of existing public enterprises, caused by new legislation and also to give an insight into the current state of local public utilities providers in the field of water and waste management. The results confirm the fact that public enterprise is the most common organizational form of local public utilities providers in the field of water and waste management and lead to conclusion that in the reorganization process the majority of existing public enterprises retained the status of a public enterprise.